Detecting different stages of Alzheimer’s disease from MRI images using deep learning and computer vision techniques - Rahman, Fardin; Sharif, Sadman; Islam, Syed Shams; Tirtho, Nihad Adnan Shah; Intheshar, Md. Ashir (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.